ANALISIS SEMIOTIKA SOSIAL PEMBERITAAN KASUS KORUPSI E-KTP DI SITUS LIPUTAN6.COM - Ayu Kumala Sari; Sapta Sari; Bayu Risdiyanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
This research is motivated by the E-KTP corruptionnewscases reported by Liputan6.com, in reporting cases of corruption E-ID card is a case that has since 3 (three) years ago investigated by the Commission and has not been resolved until today and had 2 (two ) the person determined to be a suspect and many witnesses who have been examined by the Commission graft procurement project E-KTP. This study aims to determine Domain Discourse, Subject Discourse and Tools Discourse in reporting corruption cases E-KTP in Liputan6.com site. The method used is a qualitative research MAK Halliday social semiotic approach in defining the text of a news and review thesystem in the form of sign language generated by humans. The results of this study indicate that there are three different contexts, namely the Domain Discourse, Subject Discourse and Tools Discourse. In the Domain Discourse that made Nazaruddin words that reveal there is a flow of funds E-ID card project to a certain political parties who sit in the House. The immediate goal is that people or readers know that this case is a big and difficult cases handled by KPK today. Long-term goal is this news or placed on online media sites so that people can read anytime and anywhere. Subject Discourse in this newsthat is quoted were Nazaruddin, Novanto, Febri Diansyah, Sugiharto, Ganjar Pranowo, Markus Nari, Chairuman Harahap, Junaidi, Elza Syarif, Basaria Panjaitan, and Irman. Their role there is a witness, a suspect, spokesman and lawyers. Some social distance among them which has a distance and tone; others have a relationship like Nazaruddin, Novanto, Ganjar Pranowo, Chairuman Harahap, and Markus Nari had worked a member of DPR Commission II. Irman, Sugiharto, and Junaidi both working at the Ministry of Internal Affairs. Febri Diansyah and Basaria Panjaitan was KPK spokesman. Elza syarif was attorney Nazaruddin. Furthermore tools discourse in this news style of language used is Eufisme, Aptronim, Apofasis, Majas Tautology, Contradiction Minus And Ellipsis. What type of interaction is dialogical. The medium used is writing. Channels visual form because this story was written, and only can be seen. Rhetorical mode that is used is persuasive because it aims to influence the attitudes of the public and readers to always follow the news. Keywords: Liputan6.Com, E-KTP Corruption News, MAK Halliday